Aldehyde Dehydrogenases in Arabidopsis thaliana: Biochemical Requirements, Metabolic Pathways, and Functional Analysis - Stiti, Naim; Missihoun, Tagnon D.; Kotchoni, Simeon; Kirch, Hans-Hubert; Bartels, Dorothea (Frontiers in Plant Science, 2011)
Aldehyde dehydrogenases (ALDHs) are a family of enzymes which catalyze the oxidation of reactive aldehydes to their corresponding carboxylic acids. Here we summarize molecular genetic and biochemical analyses of selected Arabidopsis ALDH genes. Aldehyde molecules are very reactive and are involved in many metabolic processes but when they accumulate in excess they become toxic. Thus activity of aldehyde dehydrogenases is important in regulating the homeostasis of aldehydes. Overexpression of some ALDH genes demonstrated an improved abiotic stress tolerance. Despite the fact that several reports are available describing a role for specific ALDHs, their precise physiological roles are often still unclear. Therefore a number of genetic and biochemical tools have been generated to address the function with an emphasis on stress-related ALDHs. ALDHs exert their functions in different cellular compartments and often in a developmental and tissue specific manner. To investigate substrate specificity, catalytic efficiencies have been determined using a range of substrates varying in carbon chain length and degree of carbon oxidation. Mutational approaches identified amino acid residues critical for coenzyme usage and enzyme activities.